An Analysis Of Errors In Descriptive Texts Composed By Tenth-Grade Students At SMKN 5 Palu - Putri Ramadhani Imsaqiah, Wanda; Darmawan, Darmawan; Wahyudin, Wahyudin; Mafulah, Mafulah (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the types and frequencies of linguistic errors found in descriptive texts written by tenth-grade students of SMKN 5 Palu. The research employs a descriptive qualitative method to analyze students’ written work using the error taxonomy proposed by Dulay, Burt, and Krashen (1982), which categorizes errors into omission, addition, misformation, and misordering. Data were collected from 32 students who completed a writing task focused on descriptive text production. The findings reveal a total of 278 errors across all samples, with misformation errors being the most prevalent (36.69%), followed closely by omission errors (35.25%). Addition errors accounted for 15.47%, while misordering errors represented 12.59% of the total errors. These results indicate significant challenges among students in applying correct grammatical structures, vocabulary, and sentence organization when writing descriptive texts. The study underscores the need for more focused instruction in grammar, vocabulary development, and writing practice to help students improve their descriptive writing skills. Additionally, the findings suggest that error analysis can serve as an effective diagnostic tool for identifying students’ writing difficulties and guiding targeted pedagogical interventions. Overall, this research contributes valuable insights into the nature of writing errors in Indonesian EFL classrooms and highlights the importance of tailored instructional approaches to enhance students’ writing competence.